Lights Off for Arbuscular Mycorrhiza: On Its Symbiotic Functioning under Light Deprivation - Konvalinková, Tereza; Jansa, Jan (Frontiers in Plant Science, 2016)
Plants are often exposed to shade over different time scales and this may substantially affect not only their own growth, but also development and functioning of the energetically dependent organisms. Among those, the root symbionts such as arbuscular mycorrhizal (AM) fungi and rhizobia represent particularly important cases – on the one hand, they consume a significant share of plant carbon (C) budget and, on the other, they generate a number of important nutritional feedbacks on their plant hosts, often resulting in a net positive effect on their host growth and/or fitness. Here we discuss our previous results comparing mycorrhizal performance under different intensities and durations of shade (Konvalinková et al., 2015) in a broader context of previously published literature. Additionally, we review publicly available knowledge on the root colonization and mycorrhizal growth responses in AM plants under light deprivation. Experimental evidence shows that sudden and intensive decrease of light availability to a mycorrhizal plant triggers rapid deactivation of phosphorus transfer from the AM fungus to the plant already within a few days, implying active and rapid response of the AM fungus to the energetic status of its plant host. When AM plants are exposed to intensive shading on longer time scales (weeks to months), positive mycorrhizal growth responses (MGR) are often decreasing and may eventually become negative. This is most likely due to the high C cost of the symbiosis relative to the C availability, and failure of plants to fully compensate for the fungal C demand under low light. Root colonization by AM fungi often declines under low light intensities, although the active role of plants in regulating the extent of root colonization has not yet been unequivocally demonstrated. Quantitative information on the rates and dynamics of C transfer from the plant to the fungus is mostly missing, as is the knowledge on the involved molecular mechanisms. Therefore, these subjects deserve particular attention in the future.